Tooth loss and periodontitis by socio-economic status and inflammation in a longitudinal population-based study - Buchwald, Sabine; Kocher, Thomas; Biffar, Reiner; Harb, Ali; Holtfreter, Birte; Meisel, Peter (Journal of clinical periodontology, 2013)
Aim To examine the associations between factors of socio‐economic status (SES), systemic inflammation and the progression of periodontitis and incidence of tooth loss. Material and Methods Data of 2566 participants from the Study of Health in Pomerania (SHIP) with a 5‐year follow‐up were analysed. We evaluated attachment loss and tooth loss with regard to social variables including education, income, marital status and related risks such as smoking and obesity. Results Socio‐economic factors were associated with the progression of attachment level and tooth loss during the follow‐up period. Low education and low income were associated with tooth loss (incidence risk ratio IRR 1.63, p < 0.001 and 1.25, p < 0.001 respectively) and also progression of mean clinical attachment level (p < 0.010 and p = 0.046 respectively). SES as well as smoking and obesity were also associated with increased levels of C‐reactive protein (CRP) with effect modifications between SES factors and CRP, also between gender and marital status. Tooth loss was associated with disadvantageous SES, particularly under conditions of high CRP levels (p < 0.001). Conclusions The progression of periodontal disease is influenced by socio‐economic factors. Effect modifications of socio‐behavioural factors by CRP indicate that under conditions of systemic inflammation adverse SES effects may be aggravated.